DETERMINANT FACTORS OF FINANCIAL REPORTING QUALITY AND ECONOMIC CONSEQUENCES - Fanani, Zaenal (University of Merdeka Malang, 2011)
The aim of this research was to prove empirically the determining factors that influence the quality of financialreporting and the economic consequences, and there were influence differences of quality attributes of financialreporting to the economic consequences. The research samples were taken by purposive sampling so it obtained141 listed manufacturing businesses from 2001 to 2006. The research used four data analysis technique:auxiliary regression R2, confirmatory factor analysis, simple regression, and multiple regressions. The resultsshowed seven attributes, there were five attributes that gave contribution for financial reporting quality namelyaccrual quality, predictability, smoothness, relevance value, and conservatism while the persistence and timelinessgave small contribution. The five attributes were also different each other. From the thirteen determiningfactors, it showed nine factors that produced significant influences namely operation cycle, sales volatility,firm size, firm age, loss proportion, leverage, environmental risk, institutional ownership, market concentration,and auditor quality, while the other three, they were liquidity, managerial ownership, and investmentgrowth that were not significant. Testing results of economic consequences of quality of financial reportingshowed that the quality of factorial financial reporting influenced negatively and significantly toward informationasymmetry.